The Chinese revolutionary army in the reform era, 1985-2010 - Genevaz, J (2014)
This thesis studies the way that the single-party state has renovated the political identity of the armed forces in the reform era of the People’s Republic of China (PRC). It argues that the Chinese Communist Party succeeded in doing so and therefore was able to use the national military as a prop of continued single-party rule. Engaging with theories of civil-military relations, this study challenges the dominant view of military professionalism according to which an armed force must be separate from politics to become truly professional. I show that the People’s Liberation Army (PLA) professionalization process, triggered by the establishment of the National Defense University in 1985, was completed by 2010, when the National Mobilization Law was issued. It provided the PLA with clear responsibility, esprit de corps, and area of expertise, these three core components of professionalism being put under firm regulatory control. This process, however, was not isolated from the political developments under way in the PRC during the same period. Instead, the ruling party turned the military into an active agent of its ‘spiritual civilization’ policy by tying it more closely to local governments, by giving it the duty to teach civic education to university students and the wider population, and by committing an increasing number of troops and other PLA resources to the United Nations peacekeeping program. This work is based on an extensive reading of the untranslated literature published, mainly, by the PLA itself, to account for the way that it adapted its tradition of ‘political work’ (the system of indoctrination and human resource management linking it to the ruling party) to the requirements of military professionalism. I completed this account with about 60 interviews with Chinese serving and retired military personnel, foreign military attachés, and students with experience of military training in Chinese universities.